Solar Watch Multipurposes (SPM) / Alya Syahira Mohd Azmi - Mohd Azmi, Alya Syahira (2020)
ASAZ Sdn. Bhd offers electronic products and services for customers, providing the variety of colours and cool design that the gives high satisfaction of consumer. Our clients are customers identifying as adult men and women who want consume product with affordable price of product. We also targeting busiest workers because we have online seller of our product to customer’s home. ASAZ offers a smart watch multipupose that give more benefits to the users. Across Malaysia and Selangor particularly the ASAZ Sdn. Bhd. business has seen an explosion of growth over the year. Selangor is an area that many gadget places in and while there are currently three businesses like us in Selangor but we only did business have special delivery services and shirt technologies. ASAZ Sdn. Bhd. marketing strategy is to emphasize the quality and price of our products and services. We offer the affordable price and we develop marketing strategy that gives attraction to come our shop and buying through online. The management of ASAZ Sdn. Bhd. consists of 6 top management Our workers have extensive experience in finance, businesses, sales and accounting. Six partners will be take role responsibilities together instead different duties and portfolio of partners. Moreover, we have service and products commitments plan to aggressively build our brand through newspaper, ads and signboard. The Smart Watch Mulitpurpose that ASAZ Sdn. Bhd. will provide is sure to appeal to customers throughout the Malaysia especially Selangor area.